Caribbean Plate margin evolution: constraints and current problems - G. GIUNTA; L. BECCALUVA; F. SIENA (Geologica Acta, 2006)
Oceanic crust was generated at multiple spreading centres during the Jurassic and Early Cretaceous, forming a “proto-Caribbean” oceanic domain. During the Cretaceous, part of that crustal domain thickened into an oceanic plateau, of petrologic Mid-Ocean Ridge (MOR) to Ocean Island Basalt (OIB) affinity. Simultaneously, the South and North American continental plates developed rifting and tholeiitic magmatism in the Middle America region (Venezuela and Cuba). The rifting created space for the proto-Caribbean oceanic domain. Petrological and regional correlations suggest that, beginning in the Cretaceous, the proto-Caribbean domain was involved into two main stages of subduction, referred to as first and second “eo-Caribbean” phases. Each phase is characterized by oblique convergence. The older (mid-Cretaceous) stage, involved in subduction (probably eastward dipping) of thin proto-Caribbean lithosphere, with generation of Island Arc Tholeiitic (IAT) and Calc-Alkaline (CA) magmatism, accompanied by high pressure - low temperature (HP - LT) metamorphic effects, and formation of arc units and ophiolitic melanges (Guatemala, Cuba, Hispaniola and Puerto Rico, in the northern margin; Venezuela in the southern). The Late Cretaceous second stage consisted of westward dipping intra-oceanic subduction; it is recorded by tonalitic arc magmatism related to the onset of the Aves - Lesser Antilles arc system. Since the Late Cretaceous, the inner undeformed portions of the Caribbean oceanic plateau (i.e. the Colombian and Venezuelan Basins) were trapped east of the Pacific subduction of the Chortis, Chorotega and Choco blocks, ultimately building the Central American Isthmus. From Tertiary to Present, continuous eastward movement of the Caribbean Plate with respect to the Americas, gave rise to transpression along both the northern and southern margins, marked by scattered and dismembered ophiolitic terranes.